CoQ deficiency causes disruption of mitochondrial sulfide oxidation, a new pathomechanism associated with this syndrome. Issue 1 (17th November 2016) - Luna‐Sánchez, Marta; Hidalgo‐Gutiérrez, Agustín; Hildebrandt, Tatjana M; Chaves‐Serrano, Julio; Barriocanal‐Casado, Eliana; Santos‐Fandila, Ángela; Romero, Miguel; Sayed, Ramy KA; Duarte, Juan; Prokisch, Holger; Schuelke, Markus; Distelmaier, Felix; et al.
Abstract: Coenzyme Q (CoQ) is a key component of the mitochondrial respiratory chain, but it also has several other functions in the cellular metabolism. One of them is to function as an electron carrier in the reaction catalyzed by sulfide:quinone oxidoreductase (SQR), which catalyzes the first reaction in the hydrogen sulfide oxidation pathway. Therefore, SQR may be affected by CoQ deficiency. Using human skin fibroblasts and two mouse models with primary CoQ deficiency, we demonstrate that severe CoQ deficiency causes a reduction in SQR levels and activity, which leads to an alteration of mitochondrial sulfide metabolism. In cerebrum of Coq9 R239X mice, the deficit in SQR induces an increase in thiosulfate sulfurtransferase and sulfite oxidase, as well as modifications in the levels of thiols. As a result, biosynthetic pathways of glutamate, serotonin, and catecholamines were altered in the cerebrum, and the blood pressure was reduced. Therefore, this study reveals the reduction in SQR activity as one of the pathomechanisms associated with CoQ deficiency syndrome. Synopsis: Disruption of the mitochondrial hydrogen sulfide oxidation pathway is identified as a new pathomechanism associated with primary CoQ deficiency. These findings may help explain the clinical heterogeneity of this syndrome. For the first time, disruption of mitochondrial sulfide metabolism is found to be associated with primary CoQ deficiency. Sulfide:quinone oxidoreductase (SQR) deficiency was related to residual CoQ levels and, as a consequence, thiosulfate sulfurtransferase (TST) activity was increased and the levels of thiols were modified. Due to the accumulation of hydrogen sulfide, the levels of certain neurotransmitters in the cerebrum of Coq9R239X mice were altered and the blood pressure was reduced. Abstract : Disruption of the mitochondrial hydrogen sulfide oxidation pathway is identified as a new pathomechanism associated with primary CoQ deficiency. These findings may help explain the clinical heterogeneity of this syndrome.